2017
DOI: 10.17159/sajs.2017/20160260
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of wild medicine harvesters from Cape Town, South Africa

Abstract: Cape Town is a fast-growing cityscape in the Cape Floristic Region in South Africa with 24 formally protected conservation areas including the World Heritage Table Mountain National Park. These sites have been protected and managed as critical sites for local biodiversity, representing potentially one-third of all Cape Floristic Region flora species and 18% of South Africa’s plant diversity. Cape Town is also inhabited by a rapidly growing culturally and economically diverse citizenry with distinct and potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…These results are supported by Rankoana (2016) who also found that restrictions on the cutting of live plants is common in the rural areas of Limpopo Province. Some of these traditional rules are common to other parts of South Africa (Petersen et al 2017) and other African countries, such as Kenya (Monica et al 2016) and Tanzania (Kangalawe et al 2014), though different rules have been reported by other studies, especially in South Africa. In the Vhembe District, for example, collection of species, including Brackenridgea zanguebarica is allowed under the supervision of an officer from the tribal authority to ensure sustainability (Tiawoun et al 2019).…”
Section: The Use Of Traditional Rules As a Management Toolmentioning
confidence: 91%
See 2 more Smart Citations
“…These results are supported by Rankoana (2016) who also found that restrictions on the cutting of live plants is common in the rural areas of Limpopo Province. Some of these traditional rules are common to other parts of South Africa (Petersen et al 2017) and other African countries, such as Kenya (Monica et al 2016) and Tanzania (Kangalawe et al 2014), though different rules have been reported by other studies, especially in South Africa. In the Vhembe District, for example, collection of species, including Brackenridgea zanguebarica is allowed under the supervision of an officer from the tribal authority to ensure sustainability (Tiawoun et al 2019).…”
Section: The Use Of Traditional Rules As a Management Toolmentioning
confidence: 91%
“…According to Rasethe et al (2013), Rankoana (2016), Petersen et al (2017) and van Wyk and Prinsloo (2018), local people in South Africa may employ simple, effective, and affordable measures to manage their natural resources such as local rules and taboos. The system of managing natural resources is termed a bottom-up approach, because locals control resources in their immediate vicinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this study also revealed that the indigenous people of the Limpopo Province, who depend on the recorded wild plant resources for survival, have evolved ways of managing them ( Table 1). Generally, traditional leaders (i.e., chiefs and headmen) are the ones managing the utilization of these resources via traditional rules and regulations, and this is common practice in other provinces of South Africa [75] and other African countries [76]. On the contrary, Kepe [77] found that in areas that are held as common property by all villagers in Mkambati area of the Eastern Cape Province (South Africa), people do not have to ask for permission to collect wild plant resources.…”
Section: Traditional Plant Conservation Strategiesmentioning
confidence: 99%
“…This has led to an increase in the numbers of wild plant harvesters, backyard medicinal plant gardens, and small holdings of selected medicinal plants, cottage processors and traders. An entire value chain for medicinal plants has developed to meet the needs of many millions traditional-remedy consumers in Southern Africa (Petersen et al, 2017). Evidently, the demand for medicinal and aromatic plants have grown rapidly because of accelerated local, national and international interest.…”
Section: Usefulness Of Medicinal Plants In South Africamentioning
confidence: 99%